Systematic Literature Review of Market Efficiency in Developing Countries - Anita; Arsyam, Ulfanita; Indrijawati, Aini; Ferdiansah, Muhammad Irdam (Muhasabatuna : Jurnal Akuntansi Syariah, 2025)
This study aims to examine market efficiency in developing countries through the Systematic Literature Review (SLR) approach by reviewing 30 scientific articles based on Scopus data and published in the last ten years (2015–2025). Market efficiency is an important concept in modern finance that reflects the extent to which asset prices reflect available information. The results of the study indicate that developing country markets generally have not achieved overall efficiency, either in weak-form or semi-strong form, and are still colored by various market anomalies such as price predictability, seasonal effects, and information asymmetry. This study identifies five main groups of determinants that influence market efficiency, namely market microstructure factors, institutions and regulations, company financial characteristics, macroeconomic dynamics and crises, and investor behavior. These findings emphasize that market efficiency in developing countries is partial, dynamic, and highly influenced by local structural and institutional conditions. The practical implications of these results can be the basis for formulating policies to improve transparency, information quality, and market governance in order to achieve more optimal and sustainable efficiency.